2012
DOI: 10.5152/jaem.2012.019
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle Related Injuries in Adults and Children in the Central Anatolian Region: Analysis of 4 Years

Abstract: Objective: We aimed to investigate and compare the features of child and adult injuries due to bicycle accidents admitted to our emergency department. Material and Methods:The study was carried out retrospectively by searching the files of patients admitted to the emergency department due to bicycle accidents in the emergency department and archive records between the dates of January 2005-December 2008. The patients were divided into two groups as adults and children. Age and sex of the patients, season or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, most of the big cities in Turkey are faced with growing traffic congestion and air pollution. In recent years, increasing the use of bicycling as a principal mode of transportation for reducing traffic congestion and air pollution and enhancing physical fitness has been discussed (Motorcycle Industry Association, 2010; Ozkan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the big cities in Turkey are faced with growing traffic congestion and air pollution. In recent years, increasing the use of bicycling as a principal mode of transportation for reducing traffic congestion and air pollution and enhancing physical fitness has been discussed (Motorcycle Industry Association, 2010; Ozkan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, more research has been on characteristics of bicycle-related and motorcycle-related traffic injuries than factors that affect helmet use (Guzel et al, 2006;Kocak, Ucar, Bayır, & Ertekin, 2010;Ozkan et al, 2012). Studies conducted in northwest (Guzel et al, 2006) and middle (Ozkan et al, 2012) Turkey that investigated injuries due to bicycle accidents admitted to hospital emergency departments showed that a great majority of injured patients were children and predominantly male. In two studies (Guzel et al, 2006;Kocak et al, 2010), none of those injured in bicycle crashes had a history of helmet use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Similarly, the highest rates of bicycle-related trauma admitted to pediatric emergency services in Turkey were seen in children aged 6-10 years. 24,25 Contributing to this issue, the prevalence reported in studies of bicycle-related dental trauma among individuals under the age of 18 was between 13% and 19.2%. [26][27][28] 25% of the traumatized cyclists in the current study had injuries to their jaw and facial bones.…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Heng et al, [2] the mortality rate was 1.9% (3/160) and the cause of mortality was related to head trauma. In the study performed by Özkan et al, [25] the injuries arising from bicycle accidents were analyzed and the cause of mortality was head trauma. In the study of Baschera et al, [18] the relationship between the ones wearing helmets and the ones who did not during bicycle and e-bicycle accidents were analyzed and the mortality rate in a bicycle accident was 1.2% (n=6/484) and the cause of mortality was intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%